Monitoring of Cryptosporidium and Giardia in Czech drinking water sources - Dolejs, P; Ditrich, O; Machula, T; Kalousková, N; Puzová, G (Schriftenreihe des Vereins fur Wasser-, Boden- und Lufthygiene, 2000)
In Czech raw water sources for drinking water supply, Cryptosporidium was found in numbers from 0 to 7400 per 100 liters and Giardia from 0 to 485 per 100 liters. The summer floods of 1997 probably brought the highest numbers of Cryptosporidium oocysts into one of the reservoirs sampled; since then these numbers decreased steadily. A relatively high number of Cryptosporidium oocysts was found in one sample of treated water. Repeated sampling demonstrated that this was a sporadic event. The reason for the presence of Cryptosporidium in a sample of treated drinking-water is unclear and requires further study.
Keywords: Cryptosporidium; Cryptosporidiosis; Česká republika; zásobování vodou; Czech Republic; Parasite Egg Count; Giardiasis; zvířata; Humans; mikrobiologie vody; počet parazitárních vajíček; giardiáza; rizikové faktory; Water Supply; Water Microbiology; Risk Factors; kryptosporidióza; Giardia; lidé; Animals